Radiotherapy for choroidal neovascularisation of age-related macular degeneration - Wagner, Wolfgang (Radiology and oncology (Ljubljana), 1999)
Age-related macular degeneration caused by choroidal neovascularisation is an increasing problem in ophthalmology. The results of the therapy in the past were poor or associated with a numher of side, effects. Recently, some reportshave shown a beneficial effect of low-dose irradiation. Therefore, we reviewed the data of our patients included in a pilot study to confirm the very preliminary data in literature. Fourtythree patients were irradiated witha linear accelerator (6 MV ) at a total dose of 16 Gy. Six months after irradiation, 69% of our patients maintained or improved their visual acuity. We did not observe side effects or any acute or late sequelae within a median follow-up period of 12 months.
Keywords: Age factors; Choroid; Muscular atrophy; Neovascularization, pathologic; Radiotherapy; Visual acuity